Chemical composition, antioxidant and cytogenotoxic effects of Ligularia sibirica (L.) Cass. roots and rhizomes extracts - Nicoleta Anca Şuţan; Andreea Natalia Matei; Eliza Oprea; Victorița Tecuceanu; Lavinia Diana Tătaru; Sorin Georgian Moga; Denisa Stefania Manolescu; Carmen Mihaela Topală (Caryologia, 2020)
Through time, in the traditional medicine Ligularia genus has been used as a remedy to cure several diseases and affections. The paper represents an essential step in offering more information about the antioxidant activity, chemical composition and cytogenetic activity of L. sibirica (L.) Cass. rhizomes and roots extracts. The antioxidant activity of the extracts has been achieved by analyzing the total phenolic content, total flavonoids, the organic chemical compound and trolox equivalent antioxidant capacity and their major polyphenolic constituents were quantified by liquid chromatography electrospray ionization-tandem mass spectrometry. The extracts were obtained by the Supercritical Fluid Extraction (SFE-CO2) technique, SFE-CO2 extraction with co-solvent and absolute ethanol extraction. The best results for the antioxidant activity have been fulfilled through the last two techniques. High Performance Liquid Cromatography (HPLC) has been applied in order to identify and quantify selected phenolic acids and flavonoids in the ethanolic extracts of L. sibirica (L.) Cass. The cytogenotoxic effects of the extracts completed the present study, with a furtherance of antiproliferative potential highlighted by the statmokinetic effect and an additional genoprotective effect.